2023
DOI: 10.3390/microorganisms11020514
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Affects Both Humans and Animals: What Is the Potential Transmission Risk? A Literature Review

Abstract: In March 2020, the World Health Organization Department declared the coronavirus (COVID-19) outbreak a global pandemic, as a consequence of its rapid spread on all continents. The COVID-19 pandemic has been not only a health emergency but also a serious general problem as fear of contagion and severe restrictions put economic and social activity on hold in many countries. Considering the close link between human and animal health, COVID-19 might infect wild and companion animals, and spawn dangerous viral muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 145 publications
1
7
0
Order By: Relevance
“…Next to viral shedding, we also investigated the potential for host adapted mutations of the inoculated SARS-CoV-2 virus within cats and environment. Animals that can get infected with SARS-CoV-2 and subsequently infect other animals, can potentially be a virus reservoir in which virus circulates and could acquire mutations over time [ 7 , 46 ]. In our study we observed only minimal mutations over time.…”
Section: Discussionmentioning
confidence: 99%
“…Next to viral shedding, we also investigated the potential for host adapted mutations of the inoculated SARS-CoV-2 virus within cats and environment. Animals that can get infected with SARS-CoV-2 and subsequently infect other animals, can potentially be a virus reservoir in which virus circulates and could acquire mutations over time [ 7 , 46 ]. In our study we observed only minimal mutations over time.…”
Section: Discussionmentioning
confidence: 99%
“…Limited empirical data exist regarding the transmission of zoonotic illness between people, canines, and the environment in AAI [ 16 , 21 , 22 ]. Close contact between people and their pet dogs in home environments (e.g., kissing, bed-sharing) has been identified as one zoonotic risk factor [ 23 ]. The feeding of raw animal products is another risk factor, with dogs fed raw or home-cooked food being more likely to carry zoonotic intestinal pathogens [ 19 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerable clients such as young children, older or pregnant people, and people with immune-compromisation may face an increased risk of illness following exposure to zoonoses and/or of suffering more severe illness [ 23 ], particularly if canines are permitted to lick [ 25 , 28 ]. Consequently, established guidelines in acute settings, such as the Society for Healthcare Epidemiology of America (SHAE) guidelines [ 20 ], typically recommend strict washing/grooming protocols for the canines, hand hygiene, reducing client exposure to canine saliva, and excluding the consumption of raw products of animal origin.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid spread of SARS-CoV-2 among humans has caused a surge in COVID-19 cases, posing a severe threat to the global economy and health [ 12 ]. Vaccines and antiviral drugs are urgently needed to combat this deadly disease, but their development can take months if not years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%